Cooperative learning and intercultural citizenship in private secondary schools case: Villa María del Triunfo - Campos Marquez, Carlos Argentino (2022)
The general objective of this research is to determine the relationship between cooperative learning and intercultural citizenship in 4° and 5° high school students from private educational institutions. In order to do this research, basic research was developed, at a relational level and with correlational design. The population of students from private educational institutions was 11230; from the Villa María del Triunfo district with a sample of 413 students. For informat ion collection the survey technique was used and as an instrument, the instrument of cooperative learning in educational contexts, the same ones that were applied for the collection of information and allowed to carry out the analysis. The result of the correlation between the variables cooperative learning and intercultural citizenship is the Pearson’s R 0.831, which means that it is high positive. Moreover, the p-value =0.000 is less than the level of significance (α = 0.05), therefore, it is concluded that there is a significant correlation between the variables cooperative learning and intercultural citizenship in 4° and 5° high school students from private educational institutions.